Mechanical and tribological behaviours of aluminium hybrid composites reinforced by CDA-B4C. (27th January 2020) - Manikandan, R; Arjunan, T V
Abstract: This study focuses on fabricating aluminium hybrid metal matrix composites reinforced with eco-friendly agro waste, cow dung ash and boron carbide by two stage stir casting. Weight percentage of cow dung ash and boron carbide were added in ratios of 2.5:7.5, 5:5, and 7.5:2.5. The effects on mechanical properties like hardness, tensile strength, impact strength, flexural strength and wear behaviour were studied. SEM and EDX analysis were employed to study the fracture mechanism for tensile, impact and wear specimens. Optical microstructure images reveal uniform distribution of particles and XRD analysis confirms the presence of reinforcements. Increasing CDA particles has reduced the density of the hybrid composite up to 8%. A maximum increase in hardness, tensile strength and wear resistance was up to 30%, 56% and 56% respectively, and then a slight decrease in impact was found in increasing the CDA particles. Dimples, transgranular cleavage facets, cracks and micro ploughing, micro cuttings are revealed from the fractured specimens of tensile, impact and wear respectively.